Residential Bacteria on Surfaces in the Food Industry and Their Implications for Food Safety and Quality. Issue 5 (1st August 2017) - Møretrø, Trond; Langsrud, Solveig
Abstract: Surface hygiene is commonly measured as a part of the quality system of food processing plants, but as the bacteria present are commonly not identified, their roles for food quality and safety are not known. Here, we review the identity of residential bacteria and characteristics relevant for survival and growth in the food industry along with potential implications for food safety and quality. Sampling after cleaning and disinfection increases the likelihood of targeting residential bacteria. The increasing use of sequencing technologies to identify bacteria has improved knowledge about the bacteria present in food premises. Overall, nonpathogenic Gram‐negative bacteria, especially Pseudomonas spp., followed by Enterobacteriaceae and Acinetobacter spp. dominate on food processing surfaces. Pseudomonas spp. persistence is likely due to growth at low temperatures, biofilm formation, tolerance to biocides, and low growth requirements. Gram‐positive bacteria are most frequently found in dairies and in dry production environments. The residential bacteria may end up in the final products through cross‐contamination and may affect food quality. Such effects can be negative and lead to spoilage, but the bacteria may also contribute positively, as through spontaneous fermentation. Pathogenic bacteria present in food processing environments may interact with residential bacteria, resulting in both inhibitory and stimulatory effects on pathogens in multispecies biofilms. The residential bacterial population, or bacteriota, does not seem to be an important source for the transfer of antibiotic resistance genes to humans, but more knowledge is needed to verify this. If residential bacteria occur in high numbers, they may influence processes such as membrane filtration and corrosion.